Optimization of Movement Development for Cerebral Palsy (CP) Students During the Covid -19 Pandemic - Wardhani, Rr Dina Kusuma; Wuryani, Wuryani; Rusmono, Rusmono (Indonesian Journal of Early Childhood Education Studies, 2021)
These children with special needs generally have differences both physically, mentally and socially, emotionally. They require adjustments in the learning process. The adjustment is made in order to optimize their development like other children. various types of children with special needs, one of which is children who do not have physical abilities (disabled). Disability can be classified into two types, namely disorders of the function of the orthopedic limb (orthopedic disability) and disorders of the function of the limb of the nerve (neurological disability). Cerebral Palsy (CP) is a part of neurological disabilities (physical disabilities), they also do not escape the attention and reach of educational services. The purpose of this study was to optimize the mobility development abilities of Cerebral Palsy (CP) students at TKLB SLB D YPAC, South Jakarta. The development of the learning model used in this study is the ADDIE Approach (Analysis-Design-Develop-Implement-Evaluate) Learning Design Model which is strengthened by the results of the instrument validity and reliability test data. The results of presenting data are in the form of analysis results and facts that the researchers found in the field, and adjusted to the theory used in this study. The discussion on the presentation of the data is the result of analysis and facts that the researchers found in the field, and has been adjusted to the theory used in this study so that it can optimize the movement development of Cerebral Palsy (CP) students at TKLB SLB D YPAC, South Jakarta through sewing board media. After conducting research and development of the sewing board media that has been developed and proven to be effective, it can be used in optimizing the mobility development abilities of Cerebral Palsy (CP) students.